1978
DOI: 10.1002/hlca.19780610405
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Mosaic Virus as a Carrier for Small Molecules I. The preparation and characterization of a TMV/α‐melanotropin conjugate

Abstract: SummaryThe use of tobacco mosaic virus (TMV) covalently loaded with hormones or other small molecules for various purposes including receptor detection and isolation is proposed. The basic principle is that of cooperative affinity interactions involving (large) numbers of artificially introduced sites (e.g. hormones) of the modified virus on the one hand and membrane-bound sites (e.g. receptors) of a cell or of a cellmembrane particle on the other. In order to test the feasibility of such TMV/hormone conjugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Eberle et al . coupled α-MSH peptides (six to several hundred) to albumin, thyroglobulin, and tobacco mosaic virus which resulted in 1500-fold higher potency than α-MSH alone [218, 219]. Bivalent ligands were first reported in the clinic by Barb et al .…”
Section: Bivalent and Multivalent Melanocortin Ligandsmentioning
confidence: 99%
“…Eberle et al . coupled α-MSH peptides (six to several hundred) to albumin, thyroglobulin, and tobacco mosaic virus which resulted in 1500-fold higher potency than α-MSH alone [218, 219]. Bivalent ligands were first reported in the clinic by Barb et al .…”
Section: Bivalent and Multivalent Melanocortin Ligandsmentioning
confidence: 99%
“…The idea of cooperative affinity labeling was introduced in the preceding paper [ 2 ] . There, an unexpectedly strong melanophore-stimulating activity of a TMV a-melanotropin (500)4) conjugate was demonstrated, for which cooperativity is a possible explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Gel-electrophoresis at pH 6.8 showed that a certain amount of non-covalently bound ANG' was associated with the TMV. Electrodialysis [2] at pH 4.5 removed the excess ANG': 635 ANG' molecules remained (covalently) bound to the virus; however, the TMV particles were strongly damaged and degraded to RNA and capsomers as shown by EM. and by CsCl gradient centrifugation.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The first examples of a-MSH multivalent constructs consisted of several a-MSH molecules coupled to albumin, thyroglobulin, and tobacco mosaic virus, which displayed a 1,500-fold higher potency than a-MSH alone [32,33]. Further structure-bioactivity studies have demonstrated that enhanced binding affinity could also be achieved with bivalent constructs [34,35].…”
Section: Introductionmentioning
confidence: 97%